Examining the relationship between peer support and foreign language emotions in online learning: the mediating effect of self-efficacy - Huang, Yujie (Frontiers in Psychology, 2023)
Introduction With the proliferation of online learning, understanding students’ affective experiences in digital foreign language courses has become imperative. Methods This mixed-methods study investigates how peer support and self-efficacy shape the emotional experiences of 502 Chinese undergraduate students in online English courses. Quantitative analyses using surveys were conducted to examine the relationships between peer support, self-efficacy, enjoyment, and anxiety. Qualitative analyses of interviews provided additional insights. Results Quantitative analyses reveal that peer support positively predicts higher levels of foreign language enjoyment and anxiety. Self-efficacy was found to partially mediate this relationship, with peer support strengthening self-efficacy, which, in turn, positively influences enjoyment and anxiety. Qualitative analyses provide converging yet nuanced insights into how peer support enhances self-efficacy and emotions beyond the surveys. Discussion The findings provide insight into optimizing online language courses through peer support and self-efficacy development tailored to diverse student needs. Limitations around sample selection, self-reported measures, and scope of relationships examined present opportunities for future research.